The Golden Handshake and the Inland Revenue: H.M.T. v. Director of Inland Revenue - Singh, Jaginder (Journal of Malaysian and Comparative Law, 2018)
The Golden Handshake and the Inland Revenue: H.M.T. v. Director of Inland Revenue